Waria di Tengah Masyarakat Kota Bengkalis Provinsi Riau - Febriani, Norlaila; Jalil, Ashaluddin; Marnelly, T. Romi (Innovative: Journal Of Social Science Research, 2025)
This study reviews the causes of someone clarifying their status as a transgender factor. This research method is qualitative, data collection is done by observation, interviews, and documentation. The subjects in this study were 5 transgender people in the city of Bengkalis. The purpose of this study was to determine the causes of someone clarifying their status as a transgender. The results of this study show that the causes of someone being sure to clarify their status as a transgender because in addition to the nature that is innate, the more dominant causes are obtained in the family environment itself, seen from transgender people who admit that parenting and education that makes them desperate to change their appearance, lack of support from the surrounding environment also greatly influences the process of this transgender to find their true identity.